The soft edge : a natural history and future of the information revolution - Levinson, Paul (Routledge, 1997)
The Soft Edge is a one-of-a-kind history of the information revolution. In his lucid and direct style, Paul Levinson, historian and philosopher of media and communications, gives us more than just a history of information technologies. The Soft Edge is a book about theories on the evolution of technology, the effects that human choice has on this (r)evolution, and what's in store for us in the future. Paul Levinson's engaging voice guides us on a tour that explains how communications media have been responsible for major developments in history and for profound chang.